INDUSTRY 4.0 CHALLENGES AND IMPLEMENTATION IN EDUCATION SECTOR IN INDIA - P, Sivasankaran; Karthikeyan, Mr. R. (International Journal of Research -GRANTHAALAYAH, 2021)
Today’s education system has brought much advancement in using digital tools to reach the students learning and understanding in simple method of representation. In this global pandemic situation, most of the educational institutions all around the globe have switched over to digital mode of operation that is remote based learning approach. In conventional system of education, students have faced lot of pressures in listening to the normal mode of class room teaching during direct interaction, but online or remote based education learning has given some pace and flexibility to visualize the concepts as well as process much better than normal black board teaching style. Through digital mode, we can able to improve much better in presenting the concepts through video simulation in lesser time span, where as in old or traditional method of education, teacher has to put more effort in teaching the concepts to students. But today’s students are less attentive in nature. They can only able to see visually through graphics only, because that kind of education students prefer. In this paper, an attempt has been made to conduct survey through forms by collecting opinions from various respondents within the educational institutes in India. Based on the responses, business framework model is developed to implement in the real system.